2015
DOI: 10.1038/ncomms7947
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynybomycins inhibit mutant DNA gyrase and rescue mice infected with fluoroquinolone-resistant bacteria

Abstract: Fluoroquinolones are one of the most commonly prescribed classes of antibiotics, but fluoroquinolone resistance (FQR) is widespread and increasing. Deoxynybomycin (DNM) is a natural-product antibiotic with an unusual mechanism of action, inhibiting the mutant DNA gyrase that confers FQR. Unfortunately, isolation of DNM is difficult and DNM is insoluble in aqueous solutions, making it a poor candidate for development. Here we describe a facile chemical route to produce DNM and its derivatives. These compounds p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 53 publications
(89 reference statements)
1
46
0
Order By: Relevance
“…Thus, a rotatable bond and globularity analysis of antibacterial agents with Gram-positive-only activity was conducted and used to select the natural product deoxynybomycin (DNM) as a good candidate for conversion to a broad-spectrum agent. DNM has antibacterial activity through inhibition of wild-type and mutant DNA gyrase, and DNM and its derivatives are only active against Gram-positive bacteria 31,32 . DNM has no rotatable bonds and a globularity of 0.02, suggesting that the addition of an amine to a position that does not alter the DNM antibacterial activity would provide a derivative able to accumulate in and be active against Gram-negative pathogens.…”
Section: Design Of Antibiotics For Gram-negative Bacteriamentioning
confidence: 99%
“…Thus, a rotatable bond and globularity analysis of antibacterial agents with Gram-positive-only activity was conducted and used to select the natural product deoxynybomycin (DNM) as a good candidate for conversion to a broad-spectrum agent. DNM has antibacterial activity through inhibition of wild-type and mutant DNA gyrase, and DNM and its derivatives are only active against Gram-positive bacteria 31,32 . DNM has no rotatable bonds and a globularity of 0.02, suggesting that the addition of an amine to a position that does not alter the DNM antibacterial activity would provide a derivative able to accumulate in and be active against Gram-negative pathogens.…”
Section: Design Of Antibiotics For Gram-negative Bacteriamentioning
confidence: 99%
“…A DNM derivative was able to rescue mice infected with fluoroquinoloneresistant MRSA [48]. The fluoroquinolone-resistant S. aureus strains selected for resistance to DNM treatment were resensitized to fluoroquinolones because such DNM-resistant strains reverted back to wild-type GyrA Ser84 [48]. Coresistance to fluoroquinolone and DNM could not be generated in the reported study, as no resistant colony was observed on treatment with both ciprofloxacin and DNM [48].…”
Section: Mechanisms Of Resistance and Potential Counteractionsmentioning
confidence: 79%
“…A related compound, deoxynybomycin (DNM, compound 4) and its derivatives, were synthesized and found to inhibit the activity of mutant Staphylococcus aureus gyrase with the fluoroquinolone-resistant substitutions at the conserved Ser84 [48]. A DNM derivative was able to rescue mice infected with fluoroquinoloneresistant MRSA [48].…”
Section: Mechanisms Of Resistance and Potential Counteractionsmentioning
confidence: 99%
See 2 more Smart Citations